The influence of work motivation and work discipline on employee performance in PG Utama Jatiwangi - Yuliawati, Tuti; Istiqomah, Istiqomah; Kamaludin, Ahmad; Andita, Vina (Indonesia Auditing Research Journal, 2024)
(PG Utama Jatiwangi,is a company that sells house tile needs that aims to achieve profit.This study will examine the factors of work motivation and work discipline to improve company performance.Based on the results of the analysis,it is concluded that the motivation of employees at PG Utama Jatiwangi related to the instrumental dimension can be included in the sufficient category,this can be illustrated that in PG Utama Jatiwangi it is sufficient to provide bonuses to its employees,and there are development and improvement efforts in providing incentives for employee welfare.Likewise,work discipline is also positively correlated with company performance,Proportionally from the two aspects of the ability and motivation variables that most influence on employee performance at PG Utama Jatiwangi is employee motivation with an effect on employee performance variations of 45.76%,meaning that motivation contributes 45.76% to each employee performance improvement at PG.Main Jatiwangi.Work motivation and work discipline together have a direct and indirect effect on regional performance(Y) of 70.42%.Meanwhile, the magnitude of the influence of other variables not included in the study on employee performance (Y) was 29.58%.Thus, work motivation and work discipline of employees at PG Utama Jatiwangi are important aspects in shaping employee performance at PG Utama Jatiwangi. Therefore,PG Utama Jatiwangi needs to pay attention to these aspects and needs to improve them optimally,so that employees at PG Utama Jatiwangi can have optimal performance as well).